Determinants Present in the Receptor Carboxy Tail Are Responsible for Differences in Subtype-Specific Coupling of β-Adrenergic Receptors to Phosphoinositide 3-Kinase - Julie Simard; Matthieu Boucher; Rachel Massé; Terence E. Hébert; Guy Rousseau (International Journal of Cell Biology)
An agonist-occupied β2-adrenergic receptor (β2-AR) recruits G protein receptor kinase-2 (GRK2) which is recruited to the membrane. Thus, the physical proximity of activated β2-AR and PI-3K allows the activation of the latter. In contrast, it has been observed that the β1-AR is unable to activate the PI-3K/Akt pathway. We hypothesized that the difference might be due to molecular determinants present in the carboxy termini of the two β-AR subtypes. Using transiently transfected HEK 293 cells expressing either β1- or β2-AR, we also observed that in presence of an agonist, β2-AR, but not β1-AR, is able to activate the PI-3K/Akt pathway. Switching the seventh transmembrane domain and the carboxy tail between the two receptors reverses this phenotype; that is, β1×β2-AR can activate the PI-3K/Akt pathway whereas β2×β1-AR cannot. Pretreatment with pertussis toxin abolished the activation of PI-3K by β2- or β1×β2-AR stimulation. Ligand-mediated internalization of the β2-AR induced by a 15-minute stimulation with agonist was abolished in the presence of a dominant negative of PI-3K or following pertussis toxin pretreatment. These results indicate that the subtype-specific differences in the coupling to PI-3K/Akt pathway are due to molecular determinants present in the carboxy tail of the receptor and further that β2-AR activates PI-3K via a pertussis toxin-sensitive mechanism.